Real-time Monitoring of Carbon Dioxide with IoT ThingSpeak using TiO2 Thick Film Gas Sensor - Chachuli, Siti Amaniah Mohd; Ying, Wong Hui; Shamsudin, Nur Hazahsha; Coban, Omer (Journal of Engineering and Technological Sciences, 2024)
Carbon dioxide is a colorless, odorless, and non-flammable gas and is claimed to be the fourth most abundant in the earth's atmosphere. Carbon dioxide emission is mainly generated by human and animal exhalation, decomposition of organic matter, and forest fires. Moreover, human activities in the industrial sector emit high levels of carbon dioxide gas, such as through fossil fuel burning, transportation, and deforestation. It is also an asphyxiant and high exposure to it may lead to health effects in humans such as headaches, breathing difficulty, tiredness, coma, and elevated blood pressure. Therefore, in this paper, a carbon dioxide gas sensor with IoT using TiO2 is proposed to observe varying concentrations of carbon dioxide gas at room temperature. Three similar gas sensors were fabricated via screen-printing technology to compare their performance towards carbon dioxide. The hardware development consisted of an Arduino Uno R3 with ESP 8266 Wi-Fi module, wires, LCD display, red and green LEDs, and a 5V power supply. The ThingSpeak application was integrated with the gas sensor and hardware parts to monitor the carbon dioxide concentration in a real-time system. Gas sensor G1 produced the highest response and highest sensitivity with values of 2.120 and 0.245, respectively.